Analysis of different ventilation strategies and CO2 distribution in a naturally ventilated classroom. (15th August 2022) - Muelas, Álvaro; Remacha, Pilar; Pina, Antonio; Tizné, Eduardo; El-Kadmiri, Said; Ruiz, Ana; Aranda, Diego; Ballester, Javier
Abstract: CO2 monitoring has proven to be an effective and affordable way of controlling air ventilation rates, a paramount task for minimizing airborne contagions in indoor shared spaces. In this work, the CO2 distribution in a naturally-ventilated classroom has been thoroughly characterized, gaining information not only on the effectiveness of diverse ventilation strategies but also on the expected differences between CO2 values when varying the sampling location within the room. The results confirm that an adequate renewal of the air in the room requires the use of cross-ventilation, with openings in different walls. Furthermore, it was found that ventilation is optimized, for a given total opening area, when the openings are distributed as much as possible among different windows. For most of the studied conditions, a global windows opening area of 1.24 m 2 with an open door was typically enough to yield CO2 concentrations below 700 ppm. The CO2 readings displayed a noticeable and consistent dependency on the sampling height, with below-average values at 0.75 m, the highest concentrations at 1.5 m, and levels close to the average when sampling at a height of 2.2 m. For a given height, the influence of the sampling location within the room was weaker, and more dependent on the specific ventilation strategy applied. However, the tests consistently showed CO2 records significantly lower for sensors installed on the walls. Besides a detailed spatial and temporal characterization of the ventilation process under different ventilation strategies, these results are thought to provide useful and novel information for a judicious placement of CO2 monitoring systems. Highlights: Natural ventilation strategies were tested in a classroom by CO2 monitoring. Continuous and distributed cross-ventilation achieved adequate CO2 levels. 17 sensors provided detailed data on the CO2 spatial distribution inside the room. The sampling height was found to play a relevant role in CO2 readings. Sensors installed on the walls yielded lower CO2 levels than the average.